Diversity in KCS2 (Ketoacyl-CoA Synthase) of selected plants and its molecular implications: A computational analysis - GROVER, MONENDRA (The Indian Journal of Agricultural Sciences, 2014)
The majority of calories in human food are derived from plant fatty acids. Besides,plant fatty acids are also a major component of a variety of products useful to human beings such as paints, cosmetics, biofuels, lubricants, detergents and soaps. Ketoacyl-CoA synthase is a key enzyme involved in the fatty acid elongation in plants In this study, we have analyzed the diversity in the KCS2 proteins of a selected plant species. We conclude that though there are extensive similarities in the KCS2 proteins studied with respect to total number of negatively charged residues, total number of positively charged residues, and domain organization, there are notable differences for other features such as extinction coefficients, protein stability, kinase specific phosphorylation sites, number of O-GlcNAc sites, predicted sumoylation sites, residues contributing to nuclear export signal and transmemebrane helices. These differences may have repercussions for the quantitative efficiency of the 3-Ketoacyl-CoA synthase enzyme which catalyzes the condensation of c2 units to acyl coA during the fatty acid elongation process, and its regulation. This paper showcases molecular implications of diversity in KCS2 , which can be used to create a diverse genetic base for engineering KCS 2 genes.